Ultrasound and Doppler Diagnostic Capabilities of Lymph Nodes in Thyroid Cancer - Kulyk , Viktoriia; Prykhodko , Yevhenii; Antoniv, Vasyl (The Ukrainian Scientific Medical Youth Journal, 2023)
nodular lesions, autoimmune thyroiditis and neoplastic processes are the leading diseases of the thyroid gland (TG), when it is characterized by the cervical lymph nodes (LN) enlargement. They can undergo macro- and microscopic changes due to inflammatory processes of bacterial or viral origin, benign and malignant lesions of the neck, head and mediastinum. Doppler ultrasonography (US) plays a significant role among the new methods of screening for altered LN and differential diagnosis of pathological processes. The aim of this work is to determine the prospects for the use of LN lesions’ ultrasound diagnostics in inflammatory and oncological processes of the TG. Ultrasound diagnostics was performed to determine Doppler signs (EDV, PSV, RI) and changes in neck LN in 175 patients with and without TG pathologies. According to the results of histopathology, the patients were divided into 4 groups: 46 healthy patients without any thyroid pathology, 44 patients with inflammatory thyroid diseases, 42 patients with thyroid cancer but without metastatic LN involvement, 43 patients with metastatic LN involvement – Thyroid cancer. B-mode ultrasound diagnostic data demonstrated positive complementation with echostructural signs and changes in vascularization. It manifested in a wide range of velocities and atypical angioarchitectonics. 13 (31%) patients had increased vascularization with PSV – 23-45 cm/s, EDV – 14- 8 cm/s, RI – 0.32-0.46. It shows the progression of proliferative processes without necrotic changes in the hilus and its periphery. In 18 (43%) patients dynamic Doppler observation indicated the appearance of accelerated blood flow and an atypical vascular concentration outside nodular capsules. It is an indicator of the cancer spread. Color Doppler mapping and energy Doppler coding of cervical metastases are important diagnostic techniques, that qualitatively and quantitatively complements and details B-mode ultrasound diagnosis.